2003
DOI: 10.1002/arp.216
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical surveys of Bury Walls hill fort, Shropshire

Abstract: Thehillfort of BuryWallsin Shropshirehasbeen surveyedextensivelyby topographicalandgeophysical methods with the aims of recovering evidence for occupation, characterising the use of the hill fort and clarifying the chronological development of the site.Topographic surveys delineated the current extent ofthefort anditsmassivefortifications.Resistance surveysshowedseveralinterestingfeatures insidethefort, includingextensiveuse ofthegeology tomakeflattenedledgesinanotherwise quiteuneven fort interior, a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Other features noticeable in Figure 3a are the geometric high resistance features in the southeast corner. It is suggested that these are more ice-wedge polygons, as seen in the interior of the fort (Murdie et al, 2003).…”
Section: Resistance Mappingmentioning
confidence: 96%
See 2 more Smart Citations
“…Other features noticeable in Figure 3a are the geometric high resistance features in the southeast corner. It is suggested that these are more ice-wedge polygons, as seen in the interior of the fort (Murdie et al, 2003).…”
Section: Resistance Mappingmentioning
confidence: 96%
“…As described in Murdie et al (2003), Bury Walls is an Iron Age hill fort on a promontory in Shropshire. On the southern and western sides and along most of the eastern side of the promontory, the steep slopes of the escarpment protect the fort; but to the north the gently undulating land outside the defences is at similar elevations to the fort interior.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fort was re-used during the later Roman period, as indicated by two large rectangular buildings, late Roman pottery and Valentinian coinage (AD364-78). A possible late Romano-Celtic temple (originally thought to be medieval) was found during an excavation in 1930 (Morris, 1932), and a recent geophysical investigation revealed several previously unknown features (for example, a cross-dyke, internal dwellings and roads) (Murdie et al, 2003).…”
Section: Settlement and Occupation -Hillfortsmentioning
confidence: 99%
“…Breidden Hill (367 m asl) is an outcrop of basic igneous rock associated with shales, sandstones, and mudstones (Watts, 1885), and is a site of archaeological significance for Iron age and Late Bronze Age forts (Buckland et al, 2001). Nesscliffe Hill (161 m asl), the geology of which was famously described by Charles Darwin in 1831 (Herbert and Roberts, 2002), is a red sandstone escarpment that is known for an Iron Age hillfort where Late Roman artefacts have been found (Home and Jones, 1959; Murdie et al, 2003). Both hills are characterised by several introduced conifer plantations including Picea sp., Tsuga heterophylla and Pseudotsuga menziesii , estimated to have been planted in the 1800s (Linnard, 1982).…”
Section: Introductionmentioning
confidence: 99%